IDENTIFIKASI PREVALENSI DAN INTENSITAS EKTOPARASIT DAN ENDOPARASIT PADA BELUT SAWAH (Monopterus albus) - Muhammad; Efrida Pima Sari Tambunan; Syukriah (Jurnal Biogenerasi, 2026)
This study aimed to identify the types of ectoparasites and endoparasites infecting swamp eels (Monopterus albus). The research used a descriptive method with purposive sampling technique on 40 swamp eels collected from two different locations. Parasite examination was conducted microscopically using Semichen-Acetic Carmine staining. The results showed two types of ectoparasites, namely Ornithodorus sp. and Clinostomum sp., and three types of endoparasites, namely Diphyllobothrium sp., Ascaris lumbricoides, and Clinostomum sp. The prevalence and intensity of parasite infections varied among samples. This study concluded that environmental conditions and water sanitation influence parasite infections in swamp eels, therefore monitoring of eel consumption safety is necessary.